Дослідження В. А. Богусевича у Чернігові 1947 та 1949 років - Ситий, Ю.М. (Археологія і давня історія України, 2022)
Стаття присвячена дослідженням В. А. Богусевича у Чернігові у 1947, 1949 рр. Узагальнюються результати робіт, простежено у якій послідовності проводилися роботи і що впливало на підведення підсумків досліджень. Результати робіт різних років дозволяють порівнювати їх між собою і зробити висновок про накопичення археологічного досвіду. Недоліки у роботі пояснюються отриманою перед війною підготовкою та відсутністю археологічного досвіду при роботах з «сухим» археологічним шаром. The excavations of V. A. Bohusevych in Chernihiv in 1947 and 1949 are analyzed in the paper. In the first year, the work was carried out on the terrace of the Desna River — on the Сitadel (the Dytynets), Okolny Grad and near the Eletsky Monastery. On the Сitadel V. A. Bohusevych looked for the remains of a barrow cemetery and did not watch the pits of buildings deepened into earth. In 1949, the expedition managed to explore the pits of the buildings not only on the Citadel (as it was in 1947) but also on other areas in its eastern part. Works were widely carried out in the Okolny Grad which allowed to obtain materials about the planning of this part of the city outscirt. Excavations have been carried out near the Eletsky Monastery. The results of different years of research allow us to compare them and draw the conclusion — in the process of expedition participants gained some archaeological experience, began understand better the structure of the cultural layer and filling the pits of buildings. The shortcomings in the work of the head of expedition can be explained by the lack of archaeological experience in working with the «dry» cultural layer. Before the war, V. A. Bohusevych worked in Pskov and Novgorod and dealt with «wet» cultural layers and the remains of land structures. Each archeological site has its own characteristics and each researcher, starting the work, develops the methods, learns to understand these features and enriches his experience in the research process. In archeology there are no direct ways to accumulate new knowledge. New materials refute false theories, and their verification allows us to increase our understanding of the development of various parts of Chernihiv, to open new pages in its history. The first years of research by V. A. Bohusevych in Ukraine were this very period of accumulation of new knowledge, which he lacked due to low-quality training caused by poor state of archaeological science in the prewar period.